The independence of the constitutional judiciary in Iraq - Mohamed Hassan, Dr. Hadeel (The college of law and political science journal, 2023)
%HFDXVHWKH FRQVWLWXWLRQDO MXGLFLDU\ LV RQH RIWKH VWDWH·V DXWKRULWLHV DQG LWVimportance is focused on preserving the constitution and ensuring the existenceof a state of law, its independence is critical, as its absence will negate theconstitution’s preservation and supremacy, as well as the lack of guaranteeingthe existence of a state of the law in which individuals’ rights and freedoms areprotected. The constitutional drafting of texts in the effective 2005 Iraqi constitutionWKDWGHDOWZLWKWKHRUJDQL]DWLRQRIWKH)HGHUDO6XSUHPH&RXUWLQ,UDTDVZHOODVthe legislative drafting of legal texts that organized the formation of the Federal6XSUHPH&RXUWLQ,UDTDUHDPRQJWKHEDVLFJXDUDQWHHVWKDWZHUHO\RQWRHQVXUHthe independence of the constitutional judiciary. starting with Law No. 30 of the)HGHUDO6XSUHPH&RXUWRI,UDTIRUWKH\HDU2005EHIRUHEHFRPLQJPRGLÀHGE\/DZNo. 25 of 2021 WKHÀUVWDPHQGPHQWWRWKHDIRUHPHQWLRQHGFRXUWODZ DQGWRVKRZWKHOHYHORIWKH)HGHUDO6XSUHPH&RXUW·VLQGHSHQGHQFHXQGHUWKHVHODZV